Integrated Management of Flows in Petroleum Products Supply Chains in the Field of Hydrocarbons Deep Processing - Shinkevich, Alexey I.; Farrakhova, Angelika A.; Shinkevich, Marina V.; Pavlova, Adeliya V.; Vyukov, Mikhail G. (International Journal of Economics and Financial Issues, 2016)
The urgency of the problems stated in the article is reasoned by the fact that the requirements on the supply chain management system in the petrochemical industry become high on the basis of an integrated logistics concept. The purpose of the article is to develop methods to systematize the advantages of an integrated model of the petroleum products’ supply chain. The leading approach to the study of this problem is the modeling method that allows assessing of the effectiveness of petroleum products’ integrated supply chains. The article presents an analytical review of petroleum products’ market development in the Tatarstan Republic. The content of integrated control of flows in the supply chain of petroleum products in the field of hydrocarbons’ deep processing is disclosed. The submissions of the article have theoretical and practical significance for the development of models of the integrated supply chains management in the petrochemical industry. Keywords: Supply Chain, Industry, Petroleum Products, Integrated Management, Petrochemical and Gas Complex. JEL Classifications: F15, L22, M11.